’N OPINIE OOR DIE BEHAVIOURISTIESE SIENING VERSUS DIE FENOMENOLOGIE AS GRONDSLAG VIR EFFEKTIEWE OPLEIDING IN WEERMAGSVERBAND - Harmse, H. (Scientia Militaria - South African Journal of Military Studies, 2012)
(Quat homines tot senteniae) This article consists of a brief discussion on the merits of the phenomenological school of thought in comparison with the better known behaviouristical school, in creating a firm base for effective training methods within the Defence Force.